THE IMPACT OF WORK HOURS, AGE, AND BONUSES ON PRODUCTIVITY AND JOB SATISFACTION AMONG TEMPORARY WORKERS - Tulus Pujo Nugroho (Asosiasi Dosen Muda Indonesia, 2025)
Temporary workers play a vital role in various industries, yet their productivity and satisfaction are often influenced by factors such as work hours, age, and financial incentives. This study aimed to analyze the distribution and impact of these variables on temporary employees to identify trends and provide actionable insights for workforce management. Using a descriptive research design, data were collected from 80 workers categorized by work hours (30–50 hours/week), age groups (25–45 years), and bonus ranges (IDR 150,000–450,000). The analysis revealed that most workers preferred standard work hours (30–35 hours/week), younger workers aged 25–30 years dominated the workforce (32%), and the majority received bonuses in the lower range (IDR 150,000–200,000). The findings highlight the importance of moderate work hours, fair incentive systems, and age-specific strategies to enhance the productivity and satisfaction of temporary workers. This study concludes that tailored employment policies and transparent bonus structures are essential for fostering a motivated and effective temporary workforce.